Universidad e interculturalidad: encuentros y desencuentros, desafíos y esperanzas (2016)
The constitutional recognition of Colombia as a multiethnic and multicultural country raised specific demands to various sectors and areas of the country. The first one refers to the acknowledgment that the monocultural state (one God, one language, one idea of family, production or development) was not enough to describe, explain, understand and name the reality of our country. Thus, a new vocabulary arises to name the territory, the people, the actions, the forms of production, the relationship with the land, the meeting with others. And although there is a large gap between the constitutional provisions and reality, there is also progress and achievements that recognize diversity. In this paper, I focus on education, particularly higher education, based on the results of the research “Interculturality and Inclusion Policies in Colombian Universities: Lessons Learned.” My goal is to account for one way of understanding diversity in the context of university: interculturalization.